Advent of clean and green technology for preparation of low-cholesterol dairy cream powder: supercritical fluid extraction process. Issue 4 (3rd July 2018) - Ghosh, Mousumi; Srivastava Shubhangi, Chitra J; Mishra, Hari Niwas
Abstract: Objectives: Due to health issues related to cholesterol and the emphasis on manufacture of low cholesterol food products, the research was undertaken for the extraction of cholesterol from cream powder using supercritical fluid extraction (SCFE) process. Materials and Methods: Face centered composite design (FCCD) was used to design the experiments with three independent variables viz., extraction temperature (40°C–75°C), extraction pressure (100–250 bar) and dynamic time (2.5–3.5 h) taking two responses (cholesterol and fat content). The standardized flow rate and static time were 5 L/min (expanded CO2 gas) and 30 min, respectively. Response surface methodology was used for optimizing the process variables. Results: It was found that higher operating pressure, low extraction temperature and moderate amount of dynamic time facilitated the removal of cholesterol. The optimized process conditions of 75°C, 204 bar and 3.5 h dynamic time yielded 39% reduction in cholesterol content and 10.6% reduction in total fat content of the cream powder. Conclusions: Thus, a low cholesterol cream powder was developed with health benefits for people suffering from cardiovascular diseases.